PHARMACOECONOMIC SUBSTANTIATION OF APPLICATION OF GENETICALLY ENGINEERED BIOLOGICAL AGENTS IN OUT-PATIENT CONDITIONS - O. Yu. Korennova; L. V. Shukil'; S. N. Mal'tsev; I. A. Klinyshkov; N. M. Leganova; E. A. Turusheva; T. V. Kropotina (IRBIS LLC, 2016)
Objective. Carrying out of the comparative clinical and economic analysis of treatment of patients with rheumatic diseases (RD) by genetically engineered biological agents (GEBA) in conditions of round-the-clock and day-time in-patient departments.Materials and Methods. In a basis pharmacoeconomic calculations on a method "cost minimization" was put the actual quantity of patients (57 persons) with RD who had previously been initiated and carried out GEBA therapy in conditions of round-the-clock in-patient department, and then the patients for eight months were observed and treated GEBA in day-time in-patient department of budgetary establishment of public health services of Omsk region "Clinical Cardiology Clinic".Results. It demonstrated clinical efficiency of application of GEBA in conditions of a day-time in-patient department in the form of statistically significant decrease of the activity of rheumatoid arthritis, psoriatic arthritis on index DAS28 and stable effect on index BASDAI at ankylosing spondylitis with achievement of stable remission of diseases. Adverse events and adverse drug reactions of GEBA were recorded regardless of the conditions of stay of patients that testifies to identity of parameters of safety of carrying out of genetically engineered biological therapy (GEBT) in a day-time in-patient department. The economic effect of application of hospitalization replacement technologies within 8 months at 57 patients amounted to 2 072 934,1 rbl. In recalculation on quantity of patients in Omsk region (120) sum of economy of system of obligatory medical insurance will amount 4 361 142 rbl.Conclusion. The parameter of a difference of costs at treatment by GEBA of patients with RD in conditions of round-the-clock and day-time in-patient departments in system of obligatory medical insurance testifies to necessity of wide introduction for a clinical practice of hospitalization replacement technologies at treatment by GEBA of patients with RD.